"Duta" Sebagai Bentuk Fenomena Migrasi Hitam (Black Migration) (Studi Kasus: Duta Kayu Agung Sumatera Selatan) - Armansyah Armansyah; Monanisa Monanisa (Jurnal Kependudukan Sriwijaya, 2017)
Duta is the perpetrator of migration whose purpose is committing crimes abroad. Duta are wll known in the community of South Sumatra. However its existence as a shadow, because hard to find. Therefore, researchers are interested in dong research entitled "Duta as Forms Migration Phenomenon Black (Black Migration) (Case Study: Duta Kayuagung SOuth SUmatra Province). This Research aimed to reveal how the process of establishing Duta Kayuagung Ogan Komering Ilir (OKI) SOuth Sumatra Province. The method used in this study is aqualitative case study model. Researchers do data collection by observation, interviews, and documentation. Research dig up information from multiple informants and key informants from the local community by doing in-depth interviews. Data analysis was done by; 1) data reduction, 2) data display, 3)conclusion or theory. There are five process of testing the validity of data: the extension of participation, persistence observation, tringualation, peer inspection through discussion, and checking members. The result of this study indicate that there is an unwritten commitment in Duta Community about not to carry out the action in their own country, that is why the Duta only commit criems abroad. Duta was formed because their high economic pressure in the region of origin, in addition to the cost of marriage makes men had to collect mony in large numbers so that they decided to become a duta abroad